The effect of social comparison tendencies on EFL teachers’ experience of burnout and instructional self-efficacy - Niloufar Saber Gigasari; Jaleh Hassaskhah (Cogent Psychology, 2017)
Factors influencing teachers’ level of burnout have been studied by different researchers, however very few focused on the relationship among three subscales of: burnout, social comparison tendencies (upward and downward), and teachers’ instructional self-efficacy. Hypothesizing that a knowledge of the relationship between these factors may promote teachers’ mental and emotional state, and hence improve their performance in classrooms, this study explored the possible relationships between the above mentioned variables. To this end, a sample of 279 Iranian teachers (209 female, 70 male) from across the country agreed to act as the participants of this study, and provide the answers to a 46-item scale (BSCSE) which addressed their degrees of burnout, social comparison tendencies (upward and downward), and instructional self-efficacy. The analyses of the data based on the Spearman Rank Order Correlation tests indicated that there were a positive significant relationship between downward comparison and the first two subscales of burnout: exhaustion and depersonalization. In addition, teachers’ upward comparison tendency showed a positive effect on teachers’ sense of instructional self-efficacy. The findings of this study provide useful information for the EFL teachers and teacher supervisors who seek specific pedagogies that decrease the level of burnout in the educational context.